The metabolic score for insulin resistance predicts the risk of cardiovascular disease in patients with psoriatic arthritis: results from the 10-year prospective CARMA cohort - Jesús Tornero; Alba Erra; Santos Castañeda; Carolina Pérez-García; Raimon Sanmartí; Sara Marsal; Ingrid Moller; Esperanza Naredo; Miguel A González-Gay; Celia Erausquin; Olaia Fernández; Ivan Castellví; et al. (RMD Open)
Objective To evaluate the predictive value of the metabolic score for insulin resistance (METS-IR) in identifying patients with psoriatic arthritis (PsA) at high risk of cardiovascular (CV) events.Methods Assessment of patients with PsA enrolled in the Spanish prospective CARdiovascular in ReuMAtology (CARMA) project. Baseline data from 500 PsA patients without a history of CV events, chronic kidney disease, diabetes mellitus or statin use at the baseline visit were analysed. Patients were prospectively followed for 10 years in rheumatology outpatient clinics at tertiary centres. The performance of the METS-IR in predicting CV events was evaluated. METS-IR was categorised into three groups: <2.25, 2.25–2.48 and >2.48.Results Over 4788 patient-years of follow-up, 27 individuals experienced at least one CV event. The annualised incidence rate was 5.6 events per 1000 patient-years (95% CI: 3.7 to 8.2). PsA patients with CV events had significantly higher METS-IR scores than those without CV events (2.37±0.24 vs 2.26±0.19; p=0.01). In this regard, patients who had CV events were more commonly included in the METS-IR 2.25–2.48 and >2.48 categories than those without CV events (p=0.008). Adjusted regression models indicated that PsA patients with a METS-IR >2.48 at baseline had an increased risk of experiencing a CV event during the follow-up period.Conclusions In PsA patients under close observation in rheumatology units included in the prospective CARMA project, METS-IR serves as a reliable prognostic predictor of CV.